Parameter extraction method for reflection-asymmetric bianisotropic metamaterial slabs using one-port measurements. (April 2023) - Hasar, Ugur Cem; Kaya, Yunus; Ozturk, Hamdullah; Ertugrul, Mehmet; Ramahi, Omar Mustafa
Abstract: An effective microwave method is developed for extracting electromagnetic properties of bianisotropic metamaterial (MM) slabs. As a non-iterative method, it utilizes only the one-port (air-backed and metal-backed MM slab) scattering (S-) parameter measurements. This is a useful feature especially for vector network analyzers, such as MS46131A, MS46121B, and R60, performing only one-port S-parameter measurements. Electromagnetic properties of a bianisotropic MM slab formed by C-shaped resonators are measured by an X-band (8.2–12.4 GHz) rectangular waveguide setup. The effect of any gap between the short-circuit termination for metal-backed measurements and the end of the MM slab on extracted electromagnetic properties is also examined for evaluating the possible error for proposed method. Highlights: An effective method for extraction of electromagnetic properties of bianisotropic materials. The method is non-iterative and relies on explicit expressions. Only one-port measurements are required for electromagnetic characterization.